Assessing the Effectiveness of Individualised Integrated Intervention Strategies to Turn Around Slow Learners: An Experimental Study - Subramanian, Dr. S. (INDIAN EDUCATIONAL REVIEW, 2013)
Slow learners are those children who are low in achieving academic skills and often ignored by others as dull, lazy or inept in the school setting. Slow learners lag behind other students not only in academics but also in social, emotional and psychological well-being. It has been estimated that 5 to 15 per cent of school going children suffer from scholastic backwardness. The early identification of students who are at risk for educational failure is an important process that deserves much attention and research.